Dynamic Effects of Energy Consumption and Economic Growth on CO2 Emission: Testing EKC Hypothesis in Africa - Musa Muhammed; Suleiman Saad; Yusuf Isah Maikudi; Ali Baba Usman (European Scientific Journal, ESJ, 2023)
This paper focuses on using time series data on real GDP, energy consumption, and CO2 emission to examine the effect of economic growth and energy consumption on CO2 emission for a panel of 23 African countries within the period 1980–2019. The study used Pedroni (1999) approach of panel cointegration analysis to test for existence of long-run cointegration relationship between the variables.  Fixed effect model was used to test for the Environmental Kutznets Hypothesis, and income squared was included as an additional explanatory variable. The estimated empirical results for the panel of 23 African countries from fixed effect model indicates the evidence of EKC hypothesis. At the level of individual countries, there is large divergence. 13 countries show evidence of EKC, implying that CO2 emission  has fallen over the long run. As income increases, the levels of environmental damage decreases in those countries. 10 countries show opposite relationship among the variables. Based on the estimated results, it is recommended that countries should pursue economic growth policies that are not highly carbon intensive. Policy makers in these countries should adopt strategies that uses environmentally friendly technologies to decrease CO2 emission. Countries should also implement strong regulatory and market-based policies in highly energy-intensive sectors to reduce their current level of emissions and attain sustainable, environment-friendly economic growth.